Parametric of dimensional analysis on iron bath gasifier - H. Zhang (Croatian Metallurgical Society, 2022)
In this paper, an iron bath gasifier is designed to handle organic solid waste. A 1:8 water model is constructed to study the effects of the various parameters on the mixing time. The empirical formula between the mixing time and dimensionless groups was determined by multiple linear regression. The study results show that the flow rate of bottom nozzle, flow rate of side nozzle, top lance position, and tracer height have a great impact on the mixing time. By substituting previous experimental data into the empirical formula, the calculated and experimental values of the dimensionless group of mixing time are found to be highly relevant.